Arquitetura conteinerizada para plataforma de testes: coleta de dados de atividades maliciosas em sistemas industriais de água - Jorge, Carlos Henrique (2025)
Detecting malicious activities in Information Technology (IT) is a critical component of cybersecurity and is essential for identifying threats and attacks on IT systems, networks, and resources. However, security of industrial control systems, an area of increasing concern due to the convergence of IT with Operational Technology (OT), requires new approaches. This work proposes a novel containerized testbed architecture for industrial water systems, implemented using open-source software and structured according to the Purdue reference model, which is widely used in industrial control and automation systems. The architecture aims to provide a secure and efficient environment. The experiments demonstrate that the proposed architecture enables the simulation of computational devices behavior in water systems under different scenarios, allowing data to be collected for the detection of malicious activities, such as denial-of-service attacks and command injection. The results highlight the architecture’s relevance to advancing research and development efforts aimed at enhancing the security of critical water infrastructure.